Effect of Aluminum Addition on the Microstructure, Tensile Properties, and Fractography of Cast Mg-Based Alloys. (10th August 2017) - Abdelaziz, M. H.; Paradis, M.; Samuel, A. M.; Doty, H. W.; Samuel, F. H.
Abstract : The present study was performed on Mg-based alloys containing Zn and Mn. The alloys were cast in a permanent metallic mold preheated to 200°C and with a protective atmosphere of dry air, CO2, and SF6 . Two main phases are observed in the as-cast condition: Mg-Al-Zn and Mn-Al intermetallics. The size and morphology of the Mg-Al-Zn phase are significantly affected by the concentration of Al. Tensile properties, using standard ASTM B-108 samples, are directly related to the size, morphology, and density of the existing phase particles. The alloy ductility is reduced with increase in the Al concentration, whereas the ultimate tensile strength and the yield strength are more or less stable. The fracture surface of the tested tensile bars is mostly ductile for low Al-containing alloys and tends to be brittle with the increase in Al content as evidenced by an increase in the density of cleavage ruptured areas.